The art of color : the subjective experience and objective rationale of color - Itten, Johannes; Haagen, Ernst van (New York : Van Nostrand Reinhold, 1961)
This book is about: Color physics; Color agent and color effect; Concord of colors; Subjective timbre; Theory of color design; ...
Keywords: Colors; Painting; Colors; Painting -- Technique